The Mill River recluse [large type] : a novel - Chan, Darcie (Thorndike Press, 2014)
From the outside, Mill River looks like any sleepy Vermont town where everyone knows everyone and people never lock their doors. This appeals to newcomers like police officer Kyle Hansen and his daughter Rowen, who are starting over after heartache, and schoolteacher Claudia Simon, determined to reinvent herself. But there are those in Mill River who have things they wish to hide. And none more than reclusive widow Mary McAllister.